Congenital Muscular Torticollis Postural And Intrauterine Cause: Case Report - Quispe-Condori, Custodio Olsen (2015)
Congenital muscular torticollis is a well-known clinical entity since antiquity. It is characterized by a deviation of the head with tilt from the affected side; the chin rotates in the opposite direction, which occurs throughout life an important functional defect neck and considerable aesthetic defect. The risk obstetrical factors included obstetrical, maternal and fetal. A case of a newborn cesarean delivery with congenital muscular torticollis of cause postural and intrauterine, evidenced by the photo views, whose prognosis is good when the physiotherapy management starts as soon arises. The present work made in the Instituto Nacional Materno Perinatal he has objective to contribute to medical knowledge and exchanging experiences in the early diagnosis of a newborn with congenital muscular torticollis of cause postural and intrauterine and timely referral to a specialized center for its management